# -7+ 5x = 10x-2? im not sure I know its

-1, but im not sure how.

-7 + 5x = 10x - 2

Since we need to get the unknowns on one side and the knowns on the other side and change their signs:

5x - 10x = 7 - 2
-5x = 5
x = -1

wait how did you what number did you subtract or add from where? to get that? to get 5x-10x=7-2?

is this right??
-7=5x=10x-2
-7+5X-10X=10X-10X-2
-7+-5=-2
-7+7-5X=-2+7
-5X=5 X=-1

Except for typing = instead of + after the -7 in the first line,
and
-7+-5=-2 instead of -7 -5x = -2 in the third line,
the rest is OK.
You got the right answer but the intermediate steps contain errors that may just be sloppy typing

## Oh no, it seems like there was a little bit of confusion with your steps there. Let me break it down for you in a more light-hearted way:

To solve -7 + 5x = 10x - 2 equation, we want to combine like terms and get all the "x" terms on one side:

-7 + 5x = 10x - 2

Now, let's get rid of those -7 and -2 on the left side by adding 7 to both sides:

-7 + 5x + 7 = 10x - 2 + 7

That simplifies to:

5x = 10x + 5

Now, let's bring all the "x" terms to one side by subtracting 10x from both sides:

5x - 10x = 10x - 10x + 5

Which simplifies to:

-5x = 5

Lastly, we just need to solve for "x" by dividing both sides by -5:

-5x / -5 = 5 / -5

And ta-da, we get:

x = -1

So, the correct answer is indeed x = -1. Keep up the great work!

## Let's go through the steps again:

-7 + 5x = 10x - 2

To isolate the variable x, we want to get all the terms with x on one side and the constant terms on the other side.

First, let's move the term with -7 to the right side by adding 7 to both sides:

-7 + 7 + 5x = 10x - 2 + 7

Simplifying the left side and the right side:

5x = 10x + 5

Next, let's move the term with 10x to the left side by subtracting 10x from both sides:

5x - 10x = 10x + 5 - 10x

Simplifying the left side and the right side:

-5x = 5

To solve for x, divide both sides by -5:

(-5x) / -5 = 5 / -5

Simplifying:

x = -1

So, the solution to the equation -7 + 5x = 10x - 2 is x = -1.

## My apologies for any confusion caused by my previous response. Let me clarify the steps once again:

Starting with: -7 + 5x = 10x - 2

To solve for x, we want to isolate the variable on one side of the equation. Here's how to do it step by step:

1. Add 7 to both sides of the equation to get rid of the negative 7 on the left side:
-7 + 7 + 5x = 10x - 2 + 7
This simplifies to: 5x = 10x + 5

2. Next, subtract 10x from both sides of the equation to move the terms with x to one side:
5x - 10x = 10x + 5 - 10x
This simplifies to: -5x = 5

3. To further solve for x, divide both sides of the equation by -5:
(-5x)/-5 = 5/-5
This simplifies to: x = -1

So the correct solution is x = -1.

I hope this clears up any confusion. Please let me know if you have any further questions!